Dark matter in the Central Region of NGC 3256 - Israa Abdulqasim Mohammed Ali; Hwang, Chorng-Yuan; Zamri Zainal Abidin; Plunkett, Adele Laurie (Penerbit Universiti Kebangsaan Malaysia, 2018)
We investigated the central mass distribution of the luminous infrared galaxy NGC 3256 at a distance of 35 Mpc by using CO(1-0) observations of the Atacama Large Millimeter and sub-millimeter Array (ALMA) and near-IR data of the Two Micron Sky Survey (2MASS). We found that there is a huge amount of invisible dynamical mass (4.48 × 1010 ) in the central region of the galaxy. The invisible mass is likely caused by some dark matter, which might have a cuspy dark matter profile. We note that this dark matter is difficult to explain with the conventional Modified Newtonian Dynamics (MOND) model, which is only applicable at a low acceleration regime, whereas the acceleration at the central region of the galaxy is relatively strong. Therefore, this discovery might pose a challenge to the conventional MOND models.